The spectre of war : international communism and the origins of World War II - Haslam, Jonathan (Princeton studies in international history and politics., 2021)
"This book is a global history of the Interwar period, which posits a new history for the origins of the Second World War. Jonathan Haslam argues that it was not only the failures of the treaties that ended the First World War that led to the Second, as has traditionally been supposed. Rather, fear of international communism hampered the Great Powers and prevented the necessary diplomatic steps to contain the aggression of Germany and Japan to a much greater extent and much earlier in history than previous scholarship has recognized. Haslam looks at newly discovered and neglected archival materials around the world to show how communism as a social and political force shaped the politics in countries as diverse as Britain, Spain, France, as well as the U.S., China, and European colonies in the 1920s and 1930s. Both Communism and fear of communism were essential components of the period's political and class divides within Europe, the Weimar crisis, the Great Depression, and colonial conflicts around the world. These social factors formed the essential background to the grand political dramas in each country, explaining for example why France seemed timid, Britain appeased, and the U.S. self-isolated. Haslam expertly brings together domestic and international politics as well as the European and Asian theaters to shed new light on this pivotal period of history in new ways. Ultimately, he shows that international communism was much a more significant factor in the diplomatic failures that permitted Japan's increased aggression and Hitler's rise to power than was previously thought"--